The art of investigation revisited : practical tips from the experts - Binns, Chelsea A.; Sackman, Bruce (Boca Raton, FL : CRC Press, 2023)
"The Art of Investigation Revisited: Practical Tips from the Experts examines the qualities required to be a professional, thorough, and effective investigator is a follow-up to the authors highly touted book The Art of Investigation (2019). This book features a wholly new line-up of investigators, experienced professionals in the field who delve into the "soft skills" that make an investigator effective. Each chapter examines a specific quality required to be a professional, thorough, and-most importantly-successful in this challenging discipline"--
Follow-up to the authors book: The art of investigation, 2019.
Keywords: Criminal investigation; Criminal investigation -- Vocational guidance; Criminal investigation -- Case studies; SOCIAL SCIENCE / Criminology; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement